HUBUNGAN BREASTFEEDING DENGAN KEJADIAN STUNTING DI PUSKESMAS ALALAK SELATAN BANJARMASIN - Nisa, Maulidatun; Irawan, Angga; Basit, Mohammad (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2024)
Background: The incidence of stunting in Indonesia has still not reached the national target of <14%. Exclusive breastfeeding is one strategy to accelerate stunting reduction, but its coverage has still not reached the national target of 80%. One of the reasons why exclusive breastfeeding coverage is not optimal is that working mothers are busy so they do not have time to breastfeed their children. Providing breast milk using the breast pump method is a solution to continue providing exclusive breast milk to prevent stunting in children. Objective: To determine the relationship between breast feeding using the breast pump method and the incidence of stunting at the South Alalak Community Health Center, Banjarmasin. Method: Quantitative research with a correlational analytical design on 30 mothers of babies aged 6-12 months who were selected using a purposive sampling technique. Data were collected using observation sheets and analyzed using the Spearman rank test. Results: Most of the mothers, totaling 21 out of 30 samples (70%) did not breastfeed using the breast pump method and most of the toddlers, totaling 18 out of 30 toddlers (60%) were stunted children. Fisher's exact test results show a value of p = 0.000 < α 0.05, which means there is a relationship between breast feeding using the breast pump method and the incidence of stunting. Conclusion: There is a relationship between breast feeding using the breast pump method and the incidence of having stunted children. Breastfeeding facilities in the office are very necessary to support exclusive breastfeeding and prevent stunting.